CCCI metrics for the measurement of quality of e-service - Chang, Elizabeth; Hussain, Farookh; Dillon, Tharam S. (IEEE, 2005)
The growing development in web-based trust and reputation systems in the 21st century will have powerful social and economic impact on all business entities, and will make transparent quality assessment and customer assurance realities in the distributed web-based service oriented environments. The growth in web-based trust and reputation systems will be the foundation for web intelligence in the future. Trust and Reputation systems help capture business intelligence through establishing customer relationships, learning consumer behaviour, capturing market reaction on products and services, disseminating customer feedback, buyers? opinions and end-user recommendations, and revealing dishonest services, unfair trading, biased assessment, discriminatory actions, fraudulent behaviours, and un-true advertising. The continuing development of these technologies will help in the improvement of professional business behaviour, sales, reputation of sellers, providers, products and services. In this paper, we present a new methodology known as CCCI (Correlation, Commitment, Clarity, and Influence) for trustworthiness measure that is used in the Trust and Reputation System. The methodology is based on determining the correlation between the originally committed services and the services actually delivered by a Trusted Agent in a business interaction over the service oriented networks to determine the trustworthiness of the Trusted Agent.